Host Plant Resistance to Bemisia tabaci to Control Damage Caused in Tomato Plants by the Emerging Crinivirus Tomato Chlorosis Virus - Fortes, Isabel M.; Fernández-Muñoz, Rafael; Moriones, Enrique (Frontiers in Plant Science, 2020)
Tomato chlorosis virus (genus Crinivirus, family Closteroviridae) (ToCV) is rapidly emerging, causing increased damage to tomato production worldwide. The virus is transmitted in a semipersistent manner by several whitefly (Hemiptera: Aleyrodidae) species and is expanding its geographical and host ranges associated with the emergence of whiteflies of the Bemisia tabaci complex. Control is based essentially on intensive insecticide applications against the insect vector but is largely ineffective. No virus-resistant or tolerant commercial tomato cultivars are available. Recently, a B. tabaci-resistant tomato line based on the introgression of type IV leaf glandular trichomes and secretion of acylsucroses from the wild tomato Solanum pimpinellifolium was shown to effectively control the spread of tomato yellow leaf curl virus, a begomovirus (genus Begomovirus, family Geminiviridae) persistently transmitted by B. tabaci. As short acquisition and transmission periods are associated to the semipersistent transmission of ToCV, its possible control by means of the B. tabaci-resistant tomato could be compromised. Moreover, if the antixenosis effect of the resistance trait present in those tomato plants results in increased B. tabaci mobility, an increased ToCV spread might even occur. We demonstrated, however, that the use of acylsugar-producing B. tabaci-resistant tomatoes effectively controls ToCV spread compared to a near-isogenic line without type IV trichomes and acylsugar secretion. No increase in the primary ToCV spread is observed and secondary spread could be reduced significantly decreasing the incidence of this virus. The possible use of host plant resistance to whiteflies to limit spread of ToCV opens up new alternatives for a more effective control of this virus to reduce the damage caused in tomato crops.